A Review of Current Control Strategy for Single-Phase Grid-Connected Inverters - Peng Mao; Mao Zhang; Weiping Zhang; Bong-Hwan Kwon (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper gives an overview of the main current control strategy for single-phase grid-connected inverters. The model of the power circuit is first discussed. Then, a classification of current control strategy in stationary reference frame follows. This is continued by a discussion of current control structures for single phase grid-connected inverters and the possibilities of implementation in stationary reference frames. The other non-mainstream regulators were also introduced. Further on, both the model of the power circuit and current control strategy in rotating reference frame were focused on as well. The overview of control strategy for single-phase grid-connected inverters and their advantages and disadvantages were concluded in this paper.